2022
DOI: 10.1128/aem.02113-21
|View full text |Cite
|
Sign up to set email alerts
|

The Indoor Mycobiomes of Daycare Centers Are Affected by Occupancy and Climate

Abstract: Many children spend considerable time in daycare centers and may here be influenced by indoor microorganisms, including fungi. In this study, we investigate the indoor mycobiome of 125 daycare centers distributed along strong environmental gradients throughout Norway. Dust samples were collected from doorframes outside and inside buildings using a community science sampling approach. Fungal communities in the dust samples were analyzed using DNA metabarcoding of the ITS2 region. We observed a marked difference… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…Two of them are the limited accuracy of incomplete reference sequence databases and the insufficient intraspecific sequence variation in barcodes (including ITS1 and ITS2) to resolve the taxonomy at the species level, as discussed above for some common mold genera, such as Penicillium, Cladosporium, Aspegillus, and Alternaria. In this study, the percentages of non-identified OTUs were similar to those observed in other DNA metabarcoding studies [22,23], increasing considerably from the phylum (4.5%) to order (10.8%), genus (28.5%), and species (47.7%) levels. Therefore, the identity and ecology of a significant proportion of the fungi detected by DNA sequencing remain unknown.…”
Section: Pros and Cons Of Different Methods: Microscopy Vs Dna Metaba...supporting
confidence: 89%
See 4 more Smart Citations
“…Two of them are the limited accuracy of incomplete reference sequence databases and the insufficient intraspecific sequence variation in barcodes (including ITS1 and ITS2) to resolve the taxonomy at the species level, as discussed above for some common mold genera, such as Penicillium, Cladosporium, Aspegillus, and Alternaria. In this study, the percentages of non-identified OTUs were similar to those observed in other DNA metabarcoding studies [22,23], increasing considerably from the phylum (4.5%) to order (10.8%), genus (28.5%), and species (47.7%) levels. Therefore, the identity and ecology of a significant proportion of the fungi detected by DNA sequencing remain unknown.…”
Section: Pros and Cons Of Different Methods: Microscopy Vs Dna Metaba...supporting
confidence: 89%
“…In building ecology, a challenging task is to differentiate between moisture-damage indicator fungi that can colonize building materials, and grow under indoor conditions, from those widespread airborne fungi more related to outdoor air, vegetation, and the household food [13], whose distribution indoors is largely driven by stochastic processes. Previous studies have demonstrated that the indoor dust mycobiota is mainly composed of spores and hyphal fragments coming from both outdoor and indoor sources [22,23,[35][36][37]. Our study has also reflected this dual origin of the dust fungi.…”
Section: Moisture-damage Indicator Fungisupporting
confidence: 79%
See 3 more Smart Citations